Analysis of the Structure and Content of the Independent Curriculum on Basic Law of Chemistry - Sophia Elvira; Zonalia Fitriza (Universitas Riau, 2023)
The independent curriculum is a curriculum that applies due to learning loss that occurred in the 2013 curriculum during the COVID-19 pandemic. Teachers do not understand the concept of the curriculum as a whole so that the independent curriculum is difficult to understand and accept. Therefore, it is necessary to analyze the depth and breadth of the material in the independent curriculum. This study aims to describe the suitability of the structure and content of the independent curriculum on the basic law of chemistry material based on the revised bloom taxonomy, Dave and Dyers taxonomy and chemical standard textbooks. This type of research is descriptive with a qualitative approach. This study used a content structure analysis research design derived from the Model of Educational Reconstruction (MER). The results of the research obtained in structural analysis are: (1) the elements of chemical understanding are in accordance with the revised bloom taxonomy, (2) the element of process skills only dominates abstract skills, (3) the elements of the pancasila profile contain abstract skills and the realm of attitudes. Meanwhile, in the content analysis, namely: (1) the breadth of material in CP basic laws of chemistry is appropriate in the high school book from the Ministry of Education and Culture, (2) the depth of material there are some materials that are not suiTable based on the chemistry textbook written by Brady edition 7.